2005
DOI: 10.2105/ajph.2002.006254
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Medicaid Enrollment: Who Is at Risk?

Abstract: Findings highlight target groups for whom additional outreach and additional simplification policies may be most needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 14 publications
2
37
1
Order By: Relevance
“…During this 1-time increase, only 22% of children who moved to public insurance could have been classified as being crowded out, substantially less than previous estimates 5,8,26 Often overlooked in the crowd-out debate is the fact that Medicaid serves as a safety net for children and families facing falling incomes. One of the original crowd-out studies is repeatedly cited for the finding that 50% of children enrolling in Medicaid after a coverage expansion would otherwise have had or were crowded out of private coverage 27 (subsequent studies have reported a wide range of crowd-out estimates 4---6 seen by the population shift in Figure 2. With more children in lower-income households, there was likely a greater need for public insurance as a safety net.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this 1-time increase, only 22% of children who moved to public insurance could have been classified as being crowded out, substantially less than previous estimates 5,8,26 Often overlooked in the crowd-out debate is the fact that Medicaid serves as a safety net for children and families facing falling incomes. One of the original crowd-out studies is repeatedly cited for the finding that 50% of children enrolling in Medicaid after a coverage expansion would otherwise have had or were crowded out of private coverage 27 (subsequent studies have reported a wide range of crowd-out estimates 4---6 seen by the population shift in Figure 2. With more children in lower-income households, there was likely a greater need for public insurance as a safety net.…”
Section: Discussionmentioning
confidence: 99%
“…Crowd-out levels also vary depending on individual state policies, structure of Medicaid and CHIP programs, and barriers to enrollment. 13,27 The general trend nationwide is toward more children being covered by public programs, similar to Ohio. 28 We believe that our core finding that the movement of children toward public programs being driven by changing economics as opposed to increased crowd-out is likely generalizable across the United States.…”
Section: Limitationsmentioning
confidence: 99%
“…Absent some underlying health concern, it is unlikely that significant numbers of parents would intentionally lower their income to gain Medicaid for their children, particularly when the median price of insuring a child on an individual plan is less than $100 per month (eHealth, 2011, p. 13). Additionally, there are significant process barriers to enrollment in Medicaid (Stuber & Bradley, 2005) which make enrollment in the program an uncertainty; it is unlikely Muhlestein, D. B., Seiber, E. E.…”
Section: E7mentioning
confidence: 99%
“…In addition, unlike the situation with the BCCPTA, other eligibility groups in many states deal with a long and cumbersome process that requires applicants to locate different documentation necessary to verify the value of their resources. The process itself can discourage completion of the application even if people are actually eligible (Hill and Lutzky 2003;Stuber and Bradley 2005). Under the Georgia BCCPTA, income is verified by self-report and indeed, in the beginning years, there was not an assessment of financial eligibility if screened by a non-NBCCEDP provider.…”
Section: Introductionmentioning
confidence: 99%